Impact of Educational Intervention on Knowledge, Attitude and Practice among General Public Regarding Accidental Poisoning - S, Justin; C, Shobha (Indian Journal of Pharmacy Practice)
The World Health Organization and Center for Disease Control and Prevention, USA has estimated that accidental poisoning is one of the major causes of morbidity and mortality around the world and in India it accounts for 18-19% of the total poisoning cases. This study was carried out with an objective to assess the impact of education on knowledge, attitude and practice (KAP) of general public about the storage, safe handling and usage of common household poisonous substances. This study was a retrospective and prospective study carried out at select geographical areas of Mysore district and two major hospitals in the city. General public from the areas of higher incidence of poisoning was included in the study to assess the impact of education on knowledge regarding prevention of accidental poisoning using KAP questionnaire. Retrospective analysis of incidence of accidental poisoning showed that the majority of cases were from three areas of Mysore city and general public from these areas were included in the study. The knowledge, attitude and practice of general public was assessed using KAP questionnaire and it was found that baseline KAP score (22.1±5.5) of the respondents significantly improved (p<0.001) after providing education at first follow up (40.5±3.7) and second follow up (34.9±4.3). Based on the assessment of KAP questionnaire it was observed that there was a significant improvement in knowledge regarding prevention of accidental poisoning among general public after providing education.
Keywords: KAP; accidental poisoning; education; household poisonous substance; prevention; India